ANTHER DEVELOPMENT ANATOMY OF Cleome rutidosperma DC. (CLEOMACEAE) IN LOMBOK - Dewi, Chandra Puspita; Amelia, Alfiya Lita; Putri, Baiq Indra Sari; Sapitri, Dea Sinta; Wahyuzeni, Indri; Julianti, Kurnia; Nirmala, Nabila Desta; Sukenti, Kurniasih; Mulyaningsih, Tri (LPPM Universitas PGRI Semarang, 2025)
Cleome rutidosperma DC is a plant native to tropical Africa, India and Indochina, and it has become an invasive weed plant introduced to Indonesia, especially on the islands of Sumatra, Kalimantan, Java and the Lesser Sunda Islands, including Lombok, to the Australian continent. C. rutidosperma belongs to the Brassicaceae order which has cleistogamy flowers. The aim of this research is to determine the anatomical development of the C. rutidosperma anther. This observation was carried out in April-June 2024, at the Advanced Biology Laboratory, Faculty of Mathematics and Natural Sciences, Mataram University, Lombok. The samples used are flower buds of C. rutidosperma which are divided into 7 phases of development. The research results shown that anatomical structure of the anther of C. rutidosperma plants were analyzed descriptively. The results include various developments of flower buds, anther development, anther transverse slice preparations of each phase of development and anther locus of each development of C. rutidosperma plants presented in the form of images and descriptions. The results were obtained that there were changes in the structure of the anther tissue in each phase and this occurs along with the development of pollen. As the anther phase increases, the structures that make up the anther support the release of mature pollen.